P572 Partial double trisomy 9 and 13-first reported case in medical literature. (June 2019) - Mahmood, Qasim; Rai, Birendra; Betts, David; Khan, Rizwan
Abstract : Background: Both trisomy 9p and partial trisomy 13q have been recognised in past with characteristics clinical anomaly, our case is the first reported case of combined partial double trisomy involving chromosome 9p and 13q. Phenotypic Characteristics vary based on the regions of the chromosome involved and the gene dosages effect. Characteristics of our index case would not only help clinician in genotype-phenotype correlation of any such future cases but would also add up to the already described consequences in offspring of balanced reciprocal translocations in either parents Case report: A female infant was born at 41 weeks gestation by normal delivery with birth weight 3.3 kgs. The pregnancy was uneventful. Baby had an episode of hypoglycaemia during very first day of life. Physical examination of the baby revealed profound central hypotonia, head lag, low set ears, depressed nasal bridge and increased nuchal pad of fat. Cardiac examination revealed soft systolic murmur of grade 2/6 which subsequently on echocardiography was noted to arise from a small atrial septal defect. Remainder systemic examination was within normal limits. Further course in the special care baby unit was complicated by recurrent apneas, desaturations and poor feeding. She also developed symptoms of cow milk protein's intolerance and gastro oesophageal reflux later on in life. Cranial ultrasound, Electroencephalography, MRI of the brain, renal ultrasound, sleep study, Laryngo bronchoscopy, chest and thoracic inlet X-rays were all normal. Array comparative genomic hybridisation, using a 60K Agilent chip showed a gain of chromosome 9 material of approximately 30.9Mb at bands 9p24.3–9p21.1 between base pair coordinates 204193 and 31104204, and an another gain of chromosome 13 material of approximately 11.2Mb at bands 13q12.11–13q12.3 between base pair coordinates 20407295 and 31578124, with the former representing the most proximal probe on this platform. Subsequent analysis of G banded metaphase chromosomes demonstrated an abnormal female karyotype with an additional chromosome consistent with a der(13)t(9;13)(p21.1;q12). Karyotypic analysis of the parents showed that the mother carried a balanced t(9;13) translocations. Therefore the transferred genetic defect in the index case was a product of 3:1 segregation error of maternal reciprocal translocation t(9;13)(p21;q12). Conclusion: Balanced reciprocal translocations in either parents can amplify and produce unbalanced gamets leading to defective conceptus. Prenatal diagnosis is strongly recommended where balanced translocation is found in parent. Clinical features of the affected conceptus depends largely on the regions of chromosome involved.